2014
DOI: 10.1093/her/cyu015
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial outcomes of a TTM-tailored condom use and smoking intervention in urban adolescent females

Abstract: Smoking and sexual risk behaviors in urban adolescent females are prevalent and problematic. Family planning clinics reach those who are at most risk. This randomized effectiveness trial evaluated a transtheoretical model (TTM)-tailored intervention to increase condom use and decrease smoking. At baseline, a total of 828 14- to 17-year-old females were recruited and randomized within four urban family planning clinics. Participants received TTM or standard care (SC) computerized feedback and stage-targeted or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(66 citation statements)
references
References 45 publications
(74 reference statements)
2
63
1
Order By: Relevance
“…However, smokers in these studies were older ( M age = 40.48 and 44.5) and greater proportions were ready to quit. The quit rates found in this study are comparable to those of other smoking cessation intervention trials targeting young smokers varying in readiness to quit (e.g., Prochaska et al, 2015; Redding et al, 2015). It is unclear whether an intervention tailored to SGM young adults, many of whom are not ready to quit smoking, would have produced higher quit rates.…”
Section: Discussionsupporting
confidence: 77%
“…However, smokers in these studies were older ( M age = 40.48 and 44.5) and greater proportions were ready to quit. The quit rates found in this study are comparable to those of other smoking cessation intervention trials targeting young smokers varying in readiness to quit (e.g., Prochaska et al, 2015; Redding et al, 2015). It is unclear whether an intervention tailored to SGM young adults, many of whom are not ready to quit smoking, would have produced higher quit rates.…”
Section: Discussionsupporting
confidence: 77%
“…A systematic review identified online interventions based on more in-depth use of theory, and consisting of a greater number of ‘Behaviour Change Techniques’ (BCTs), as most effective at changing health behaviour [ 16 ]. Theoretically driven interventions developed to support smoking cessation have often been theory specific and typically based on the transtheoretical model (e.g., [ 17 , 18 ]). Because no one theory of behaviour change can be said to offer a complete explanation of behaviour, however, it is arguably more appropriate to select approaches that are theory agnostic [ 19 ] and encompass a range of systematically mapped theoretical concepts.…”
Section: A Theoretically Driven Behaviour Change Interventionmentioning
confidence: 99%
“…not achieved conventional measure of educational attainment on completion of compulsory schoolingMilburn 2012 [97]STRIVENewly homeless youth and their familiesMinnis 2014 [98]Yo PuedoLatino participants aged 16–21 years, residing in San FranciscoMonti 1999 [99]Alcohol Screen and B.I. 1Individuals aged 18–19 years, with drink-related emergency department attendancesMorris 2003 [100]Self-Sufficiency ProjectTargeted at low income single parent families from 2 Provinces in CanadaNewton et al 2009 [101]Climate schoolsIndependent (private) schoolsNirenberg 2013 [102]ROADTargeted to youth with a high risk driving or alcohol prior drug-related police chargeNores 2005 [103]High/Scope PerryHigh risk childrenPalinkas et al 1996 [104]Social skills trainingPregnant and non-pregnant (at risk for pregnancy) adolescents using/at risk of using drugsPantin 2009 [105]Familias UnidasHispanic adolescents in grade 8 with behavioural problems, and their primary caregiversRedding 2015 [106]Step-by-StepFemales, aged 14–17 years, not pregnantSanchez 2007 [107]Reconnecting youthTargeted to persons experimenting with drugs or other risk-related behavioursSchwinn 2010 [108]RealTeenTargeted to girls living in public subsidized housingShetgiri 2011 [109]Shetgiri StudyHigh-risk status based on:rate of absence of 80% and above, 2 or more disciplinary actions in 8th grade, failing two or more classes in 8th grade, or high levels of family dysfunction identified by grade teacher, using proxies such as multiple family moves in grade 8, perceived lack of parental involvement or family conflictSussman et al 1998 [110]Towards no drug abuse - School-as-communityContinuation high school youth at high risk of drug useTierney 1995 [111]Big Brothers Big SistersYouth from single parent households recruited for mentoringVitaro et al 1996 [112]SAPPYoung boys and girls with behaviour problems diagnosed in sampleWagner 2014 [113]Guided Self ChangeHigh risk behaviour related to alcohol and violence …”
Section: Appendixmentioning
confidence: 99%